Determinants of Subjective Emotional Well-Being and Self-Determination of Employees: Slovene Case - Simona Šarotar Žižek; Matjaž Mulej; Borut Milfelner (Naše gospodarstvo/Our economy, 2017)
Work is a crucial part of human life.One should attain employees’well-being (WB) to support organisational success. In the first phase, the confirmatory factor analysis (CFA) was employed to assess the dimensionality, reliability, and validity of the reflective latent constructs. In the second phase, structural equation modelling was performed to test the research hypotheses. By structural equation modelling we found that physical health (PH) statistically significant negatively affects subjective emotional well-being (SEWB). Positive PH and SEWB were negatively connected. Emotional intelligence (EI) has a statistically significant impact on SEWB. The last relationship in the model—between spiritual intelligence (SI) and self-determination (SD)—was negative, but statistically significant. Therefore, human resource management’s activities (HRM) must concentrate on optimal physical/mental health, emotional (EI) and spiritual (SI) intelligence. Employees’ good health supports their emotional WB. Their emotional balance, based on their EI, enhances their subjective emotional WB and SD. The employees ’SI affects their SD.